Prevalence and Severity of Anemia in Children Hospitalized with Acute Heart Failure. (8th April 2016) - Goldberg, Jason F.; Shah, Mona D.; Kantor, Paul F.; Rossano, Joseph W.; Shaddy, Robert E.; Chiou, Kevin; Hanna, Jonathan; Hagan, Joseph L.; Cabrera, Antonio G.; Jeewa, Aamir; Price, Jack F.
Abstract: Objective: Anemia is common among adult heart failure patients and is associated with adverse outcomes, but data are lacking in children with heart failure. The purpose of this study was to determine the prevalence of anemia in children hospitalized with acute heart failure and to evaluate the association between anemia and adverse outcomes. Design: Review of the medical records of 172 hospitalizations for acute heart failure. Setting: Single, tertiary children's hospital. Patients: All acute heart failure admissions to our institution from 2007 to 2012. Interventions: None. Outcome Measures: Composite endpoint of death, mechanical circulatory support deployment, or cardiac transplantation. Results: Patients ages ranged in age from 4 months to 23 years, with a median of 7.5 years, IQR 1.2, 15.9. Etiologies of heart failure included: dilated cardiomyopathy ( n  = 125), restrictive cardiomyopathy ( n  = 16), transplant coronary artery disease (n = 18), ischemic cardiomyopathy ( n  = 7), and heart failure after history of congenital heart disease (n = 6). Mean hemoglobin concentration at admission was 11.8 g/dL (±2.0 mg/dL). Mean lowest hemoglobin prior to outcome was 10.8 g/dL (±2.2 g/dL). Anemia (hemoglobin <10 g/dL) was present in 18% of hospitalizations at admission and in 38% before outcome. Anemia was associated with increased risk of death, transplant, or mechanical circulatory support deployment (adjusted odds ratio 1.79, 95% confidence interval = 1.12–2.88, P  = .011). For every 1 g/dL increase in the patients' lowest hemoglobin during admission, the odds of death, transplant, or mechanical circulatory support deployment decreased by 18% (adjusted odds ratio = 0.82, 95% confidence interval = 0.74–0.93, P = 0.002). Conclusions: Anemia occurs commonly in children hospitalized for acute heart failure and is associated with increased risk of transplant, mechanical circulatory support, and inhospital mortality.